The effect of clitoral stimulation post artificial insemination on pregnancy rates of multiparous Bos indicus beef cows submitted to estradiol/progesterone-based estrus synchronization protocol - Oliveira Filho, Ramiro; Cooke, Reinaldo F.; Mello, Gustavo A. de; Pereira, Victor M.; Vasconcelos, Jose Luiz M. [UNESP]; Pohler, Ky G. (Oxford Univ Press Inc, 2020)
Clitoral stimulation after artificial insemination (AI) in beef cattle is a common practice utilized by AI technicians; however, the effect of clitoral stimulation during fixed-time AI (TAI) is still unknown. The objective of the present experiment was to evaluate the effect of clitoral stimulation on temperament responses and pregnancy rates to TAI in Bos indicus beef cows. A total of 1,186 multiparous Nellore cows across three different locations were assigned to an estradiol/progesterone-based estrus synchronization + TAI protocol (day -11 to 0). Cows were randomly assigned to receive either 3 s of clitoral stimulation (n = 602) or no clitoral stimulation (n = 584) immediately after TAI (day 0). Cow body condition score (BCS) was recorded on day -11. Estrus expression was evaluated based on estrus detection visual aid patch activation on day 0 (estrus, >= 50% activated; no estrus, <50% activated). Temperament was assessed by individual chute score based on a 5-point scale before TAI, and individual exit velocity was measured after clitoral stimulation. Pregnancy diagnosis was performed 30 d after TAI via transrectal ultrasonography. Pregnancy rate to TAI was positively affected by BCS (P < 0.01) and estrus expression (P = 0.03). Pregnancy rates of cows receiving clitoral stimulation did not differ (P = 0.39) from cows non-stimulated (47.5 +/- 4.6% vs. 44.3 +/- 4.6%, respectively). No interaction of clitoral stimulation and estrus expression was observed (P = 0.26). Chute score was positively correlated to exit velocity (P < 0.01; r = 0.29); however, clitoral stimulation did not affect exit velocity (P = 0.86). In summary, pregnancy rates to TM are influenced by various factors and multiple strategies have the potential to increase the fertility of beef cows submitted to TM; however, clitoral stimulation of Bos indicus beef cows did not improve TAI pregnancy rate.
Keywords: beef cows; clitoral stimulation; fixed-time artificial insemination